Assessment of haemophilic arthropathy through balance analysis: a promising tool. Issue 4 (12th March 2019) - García-Massó, Xavier; Ye-Lin, Yiyao; Garcia-Casado, Javier; Querol, Felipe; Gonzalez, Luis-Millan
Abstract: The purpose of this study was to develop a tool able to distinguish between subjects who have haemophilic arthropathy in lower limbs and those who do not by analyzing the centre of pressure displacement. The second objective was to assess the possible different responses of haemophiliacs and healthy subjects by creating a classifier that could distinguish between both groups. Fifty-four haemophilic patients (28 with and 26 without arthropathy) and 23 healthy subjects took part voluntarily in the study. A force plate was used to measure postural stability. A total of 276 centre of pressure displacement parameters were calculated under different conditions: unipedal/bipedal balance with eyes open/closed. These parameters were used to design a Quadratic Discriminant Analysis classifier. The arthropathy versus non-arthropathy classifier had an overall accuracy of 97.5% when only 10 features were used in its design. Similarly, the haemophiliac versus non-haemophiliac classifier had an overall accuracy of 97.2% when only 7 features were used. In conclusion, an objective haemophilic arthropathy in lower limbs evaluation system was developed by analyzing centre of pressure displacement signals. The haemophiliac vs . non-haemophiliac classifier designed was also able to corroborate the existing differences in postural control between haemophilic patients (with and without arthropathy) and healthy subjects.